Memahami Kreativitas Ilmiah Siswa Sebagai Dasar Pengembangan Program Pembelajaran Berbasis Proyek pada Tingkat SMP di Kota Metro Lampung - Nasiruddin Nasiruddin; Noor Fadiawati; Chansyanah Diawati (Postgraduate, University of Mataram, 2023)
This research aims to find out more about teacher perceptions in students' scientific creativity as a basic for project-based learning models as well as provide information about the use of project-based learning programs that are in accordance with PjBL syntax at the junior high school level in Metro City. This research is a type of qualitative research with a case study approach, data collection techniques used are interviews (interviews), observation and documentation. Then to ensure the validity of the data using technical triangulation and source triangulation followed by data analysis with the research flow, namely identifying problems, determining research designs, determining research roles, determining data collection procedures, data recording, data analysis and verification, and narrating the research results obtained. The results of this research indicate that 54% of teachers have not used the PjBL learning model in learning and the teacher's perception of PjBL is good, but 62% of teachers do not know the PjBL syntax that must be fulfilled in using this learning model. In relation to scientific creativity, teachers do not know what indicators must exist in assessing students' scientific creativity